The heterogenous labour market impact of the COVID-19 pandemic - Guido Matias Cortes; Eliza Forsythe (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2021)
We study the distributional consequences of the Covid-19 pandemic's impacts on employment, both during the onset of the pandemic and over recent months. Using cross-sectional and matched longitudinal data from the Current Population Survey, we show that the pandemic has exacerbated pre-existing inequalities. Although employment losses have been widespread, they have been substantially larger - and persistently so - in lower-paying occupations and industries. We find that Hispanics and non-white workers suffered larger increases in job losses, not only because of their over-representation in lower paying jobs, but also because of a disproportionate increase in their job displacement probability relative to non-Hispanic white workers with the same job background. Gaps in year-on-year job displacement probabilities between black and white workers have widened throughout the course of the pandemic recession, both overall and conditional on pre-displacement occupation and industry. These gaps are not explained by state-level differences in the severity of the pandemic or the associated response in terms of mitigation policies. We also find evidence that suggests that older workers have been retiring at faster rates.
Keywords: 330; Coronavirus; Arbeitsmarkt; Beschäftigungseffekt; Qualifikation; Soziale Gruppe; USA